Sociological and theory of planned behaviour approach to understanding entrepreneurship: Comparison of Vietnam and South Korea - Phuong Mai Nguyen; Dinh Van Toan; Thi Minh Ngoc Luu; Yongshik Choo (Cogent Business & Management, 2020)
This study explains entrepreneurship in the context of a comparative analysis of Vietnam and South Korea. For that purpose, it develops an analytical framework based upon both theory of planned behaviour (TPB) and sociological approach to demonstrate whether or how much macro-environmental factors, such as entrepreneurship education, family support and social support, and the three TPB antecedents, including attitude, subjective norms and perceived behaviour control, affect entrepreneurial intention. Primary data were collected from a self-administered survey with 600 students in Vietnam and 550 students in South Korea using the convenience sampling method. Structural equation modelling (SEM) analysis was adopted to test the entrepreneurial intention model in two subsamples. Furthermore, independent sample T-test and multi-group analyses were performed to see differences in entrepreneurial intention between the two countries. This study found significant differences in the entrepreneurial intention between the two countries. In Vietnam, entrepreneurship education and family support positively affect the students' attitude towards entrepreneurship. However, among the antecedents of entrepreneurial intention, only perceived behaviour control influence their entrepreneurial intention. On the other hand, in South Korea, all the macro-environmental factors positively affect the three TPB antecedents and entrepreneurial intention. Moreover, attitude is the most influential factor in entrepreneurial intention.
Keywords: 650; entrepreneurial intention; entrepreneurship education; family support; society support; theory of planned behaviour; Vietnam; South Korea; students